A preclinical model of chronic pancreatitis driven by trypsinogen autoactivation - Andrea Geisz (Nature Portfolio, 2018)
Inflammatory diseases of the pancreas are currently untreatable and lack a pre-clinical model that recapitulates the hallmarks of the human pathology. Here, the authors generate a knock-in mouse strain with increased tripsinogen autoactivation and show that it develops spontaneous pancreatic pathology with some key features of human pancreatitis.